The Emotional Sensitivity of University Student's Girls to the Practices and Non-practices of Sport - Hind Salem Tayeh (Journal of Global Pharma Technology, 2016)
Their current research problem has focused on trying to answer the following question: Does exercise affect the emotional sensitivity of students in Iraqi universities? The objective of the study was to identify the level and fields of emotional sensitivity of both female students and non-sports practices, and to identify the differences between the level and fields of emotional sensitivity in both female and non-sports students. The researchers hypothesized the following: Of the emotional sensitivity between female students and non-practices of sport, and there are significant differences between the results of the negative field of emotional sensitivity between female students and non-practices of sport, there are differences of statistical significance between NTA The researchers used descriptive research method in the method of comparative studies on a sample of students of the third stage of the Faculty of Physical Education and Sports Sciences at the University of Baghdad (practices) for sport and the third phase students of the Faculty of Management and Economics at Mustansiriya University (Non-practices) for the sport, the number of (60) students who are 21 years of age in each of the two kidneys persisted for the academic year 2017/2018 by (30) students to exercise sports, and (30) non-sports student, Their stages of rain (SPSS). The researchers concluded that the level of emotional sensitivity in both the practices and non-practices of the sport was clear, that the level of emotional sensitivity in the practices was More than non-sports practices, female students need practices and practices to guide psychological counseling to reduce the level of emotional feeling they have, to recommend that researchers should pay attention to the measurement of emotional sensitivity to university students B Each league, interest in providing the educational atmosphere dominated by harmony and tolerance for students of Physical Education and Sports Science, it is necessary to work to enable the teaching staff in the faculties of Physical Education and Sports Science members to provide educational and psychological counseling programs and provide students with the state of love.Keywords: Emotional sensitivity, Practices and non-practices of sport.